3D PRINTING IN CONSTRUCTION AS A TOOL FOR SUSTAINABLE ARCHITECTURE - Ilkhomjon Ergashev (Modern American Journals, 2025)
The emergence of 3D printing in construction has opened a new chapter in sustainable architecture, enabling the creation of resource-efficient, environmentally responsible, and innovative building solutions. Additive manufacturing allows for the use of recycled and locally available materials, including clay, concrete waste, and biopolymers, significantly reducing reliance on energy-intensive resources. By producing only the exact volume of material required, 3D printing minimizes construction waste and contributes to lowering the overall carbon footprint of the building industry. Furthermore, additive methods facilitate the realization of energy-efficient geometries and optimized structural forms that were previously difficult to achieve with traditional methods. These qualities directly support the principles of green building certification systems, such as LEED and BREEAM, making 3D printing an important instrument for sustainable development. The scientific value of this research lies in analyzing how additive manufacturing integrates ecological responsibility, technological innovation, and architectural design to provide a comprehensive framework for sustainable architecture.
Keywords: Architecture, urban planning, 3D printing, LEED, BREEAM, green building, personalized housing, sustainable development, construction innovation.